A ação espasmolítica do óleo essencial de Lippia microphylla Cham. e de seus constituintes majoritários envolve o bloqueio do influxo de cálcio em íleo de cobaia - Oliveira, Gislaine Alves de (2014)
The essential oil extracted from aerial parts of Lippia microphylla Cham. (Verbenaceae) (LM-OE) presents as major compounds thymol and carvacrol. The aim of this study was to investigate and to characterize oil LM-OE spasmolytic effect on guinea pig ileum, as well to verify if this effect is due its major compunds, thymol and carvacrol. Were performed measures of isometric and isotonic contractions and cytosolic calcium. LM-OE inhibited phasic contractions induced by 10-6 M of histamine or carbachol (CCh) (IC50 = 15.8 ± 2.3 e 24.4 ± 2.9 μg/mL, respectively). In a similar manner, thymol, carvacrol and thymol/carvacrol mixture antagonized histamine- (IC50 = 14.2 ± 1.6; 13.6 ± 1.3 e 13 ± 2.1 μg/mL, respectively) ou CCh- (IC50 = 21.3 ± 3.8; 16 ± 2.6 e 27.9 ± 4.8 μg/mL, respectively) induced phasic contractions. Compared with LM-OE, in neither case was difference. In the same way, LM-OE relaxed pre-contracted organ by 40 mM of KCl, 10-5 M of CCh or 10-6 M of histamine (EC50 = 7.6 ± 0.8; 7.2 ± 1.3 e 6.8 ± 0.6 μg/mL, respectively), being equipotent in the three situations. As CaV are common step on pathway of these three contractile agents, we hypothesized that somehow LM-OE would blocking Ca2+ influx by these channels. Once probably the major compounds are biological markers for this specie, we evaluated their effect upon tonic contraction induced by 40 mM of KCl. We found that thymol, carvacrol and thymol/carvacrol mixture relaxed the ileum in a significant and concentration-dependent manner (EC50 = 5.1 ± 1.1; 11.5 ± 1 e 5.1 ± 1.1 μg/mL, respectively), being carvacrol the least potent among the three, they did not showed statistic difference when compared with LM-OE. To confirm the hypothesis of CaV participation on LM-OE spasmolytic action, were performed cumulative concentration-response curves to CaCl2 in a nominal without Ca2+ depolarizing medium in absence (control) and LM-OE presence, witch one antagonize these contractions besides to relaxes the organ when it was pre-contracted by S-(-)-Bay K 8644 (EC50 = 8.5 ± 1.5 μg/mL), a selective CaV 1, agonist confirming that the CaV subtype involved is CaV 1. The fact of CsCl, a K+ channels nonselective blocker, has not changed the relaxing potency of LM-OE oil on ileum pre-contracted with 10-5 M CCh, discard the hypothesis of positive modulation of these channels, which would lead to an indirect blockade of CaV. In experiments with ileum circular layer, LM-OE antagonized phasic contractions induced by 10-6 M of CCh (IC50 = 30.1 ± 1.5 μg/mL), that suggests a negative modulation of the Ca2+ intracellular signaling by LM-OE oil to exert its spasmolytic effect. Viability of layer longitudinal smooth muscle cells was evaluated in the absence and presence of 81 μg/mL LM-OE oil, and no cell death was verify during 2 h of contact with cells LM-OE oil. In the presence of LM-OE oil, the intensity of fluorescence in intestinal guinea pig myocytes stimulated by histamine was reduced as a result of the reduction of calcium cytosolic concentration ([Ca2+]c). In conclusion, the LM-OE oil act by blocking calcium influx through CaV1, possibly by inhibiting intracellular Ca2+ signaling and reducing [Ca2+]c, to promote its spasmolytic effect in guinea pig ileum